Orígenes políticos del riesgo argentino - Jorge C. Ávila (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2015)
– The purpose of the essay is twofold: a) explore the ability of S. Huntington's model of political development for societies in process of modernization to explain the Argentine political history in 1880-1955; b) prove the hypothesis that mass pretorianism is inherently unstable. We conclude the evidence supports the Huntington's model. In other words, the model explains the changes that the political system underwent in the period, as much as the growing instability between the traditional civil order of 1862-1912 and the mass pretorian order of 1946-1955. Furthermore, we show that Argentine risk was high for mass pretorian orders and relatively low for civil orders and (radical and oligarchic) pretorian orders. It seems that the fiscal deficit plays an important role in connecting the political regime with Argentine risk.
Keywords: P16; 330; Länderrisiko; Diktatur; Politische Partizipation; Haushaltsdefizit; Geschichte; Finanzgeschichte; Argentinien